Pengaruh Circuit Training Terhadap Kekuatan Fisik Pada Atlet Sekolah Sepakbola (SSB) Persisac Semarang - Umar Fitriadi Umar Fitriadi (YLPK Mahardhika, 2021)
Circuit Training is a form of training in which there are various movements that are carried out together and continuously and are limited by rest at each exchange of training forms with circuit training there will be many positive shifts in basic skills and also simultaneously restore physical fitness, muscle ability, endurance, dexterity and flexibility of the body. Strength needs to be given special attention from the coach so that the achievements of the SSB (Football School) Persisac Semarang do not decline. The research used in this study is